Adverse Effects of Personal Protective Equipment Among Intensive Care Unit Healthcare Professionals During the COVID-19 Pandemic: A Scoping Review. (June 2021) - Unoki, Takeshi; Sakuramoto, Hideaki; Sato, Ryuhei; Ouchi, Akira; Kuribara, Tomoki; Furumaya, Tomomi; Tatsuno, Junko; Wakabayashi, Yuki; Tado, Asami; Hashimoto, Naoya; Inagaki, Noriko; Sasaki, Yoshiko; et al.
Introduction: To avoid exposure to SARS-COV-2, healthcare professionals use personal protective equipment (PPE) while treating COVID-19 patients. Prior studies have revealed the adverse effects (AEs) of PPE on healthcare workers (HCWs); however, no review has focused on the AEs of PPE on HCWs in intensive care units (ICUs). This review aimed to identify the AEs of PPE on HCWs working in ICUs during the COVID-19 pandemic. Methods: A scoping review was conducted. MEDLINE, CINAHL, the World Health Organization (WHO) global literature on COVID-19, and Igaku-chuo-zasshi (a Japanese medical database), Google Scholar, medRxiv, and Health Research Board (HRB) open research were searched from January 25–28, 2021. The extracted data included author(s) name, year of publication, country, language, article title, journal name, publication type, study methodology, population, outcome, and key findings. Results: The initial search identified 691 articles and abstracts. Twenty-five articles were included in the analysis. The analysis comprised four key topics: studies focusing on PPE-related headache, voice disorders, skin manifestations, and miscellaneous AEs of PPE. The majority of AEs for HCWs in ICUs were induced by prolonged use of masks. Conclusion: The AEs of PPE among HCWs in ICUs included heat, headaches, skin injuries, chest discomfort, and dyspnea. Studies with a focus on specific diseases were on skin injuries. Moreover, many AEs were induced by prolonged use of masks.